Less or more widely studied languages – How has language specialist education in Finland changed in twenty years? - Veivo, Outi; Norro Soili; Johansson, Marjut (Peter Lang, 2026)
In recent decades, language education has undergone many changes in Finnish primary and secondary schools in such a way that it has had an impact on the study of foreign languages. Also, in Finnish higher education, language degree programmes have been the object of various reforms and language policy measures. The objective of this article is to discover whether these changes are reflected in the number of new students entering language specialist education. By analysing the distribution of new students across different language degree programmes, we aim to characterize which languages are less and which are more widely studied in the Finnish higher education context. Our aim is also to discover whether the situation has changed over the last twenty years. Our results show that the proportion of English language students has grown at the expense of other languages, such as Swedish, German and French. These findings are discussed in the framework of educational and national language policies.
Linguistic and Intercultural Landscapes in the European Higher Education